2017
DOI: 10.5792/ksrr.16.045
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Results of Oxford Medial Unicompartmental Knee Arthroplasty in Young Asian Patients Less than 60 Years of Age: A Minimum 5-Year Follow-up

Abstract: PurposeThe purpose of this study was to evaluate the efficacy of unicompartmental knee arthroplasty (UKA) in young active Asian patients by analyzing clinical outcomes, complications and survival rates.Materials and MethodsEighty-two knees were evaluated with a minimum follow-up of 5 years after Oxford phase 3 UKA in patients less than 60 years of age at the time of surgery. Their mean age was 54.7 years (range, 44 to 59 years). The mean follow-up period was 8.9 years (range, 5.3 to 12 years). Kaplan–Meier sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
0
29
1
1
Order By: Relevance
“…Several recent studies have shown clinical outcome of UKA comparable to those of total knee arthroplasty in less than 60-year-old patients 1 , 14 , 16 18) . In a study by Pennington et al 6) , UKA using fixed bearing Miller-Galante prostheses resulted in excellent outcomes in 93% of the less than 60-year-old patients: the mean Hospital for Special Surgery knee score was 94 points and the mean UCLA activity score was 6.5 points at a mean of 11-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown clinical outcome of UKA comparable to those of total knee arthroplasty in less than 60-year-old patients 1 , 14 , 16 18) . In a study by Pennington et al 6) , UKA using fixed bearing Miller-Galante prostheses resulted in excellent outcomes in 93% of the less than 60-year-old patients: the mean Hospital for Special Surgery knee score was 94 points and the mean UCLA activity score was 6.5 points at a mean of 11-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Примером хороших результатов и 5-летней выживаемости ОЭКС медиального отдела может служить исследование ученых из Кореи [23]. По данным T. Xu с соавторами, 6-и 8-летняя выживаемость эндопротеза Oxford Phase-3 составила 97% и 93% соответственно [24], следует обратить внимание на то, что в исследовании участвовали местные жители со средним ИМТ = 24,7 кг/м 2 .…”
Section: пациентыunclassified
“…20 With the development of surgical techniques and prosthetic designs, a number of studies have been published on the good medium-and long-term outcomes of UKA in young patients. [21][22][23] Although the efficacy of UKA in patients over 60 years of age is definite and the survival rate is satisfactory, there are still different reports on the efficacy of young patients. In particular, a relatively small number of studies have been published on the Asian population.…”
Section: Introductionmentioning
confidence: 99%